Comparative Study of Purple Rice and Green Rice for Salt Stress Sensitivity - Nahar, Most. Aynun; Nahar, Mst. Nur-E-Nazmun; Prodhan, Md. Yeasin; Hoque, Md. Anamul; Rahman, Md. Shazadur (Journal of the Bangladesh Agricultural University, 2024)
Farmers of Bangladesh are cultivating an unidentified so-called purple rice (PR) having purple-colored leaf. Less information is available on PR in any areas of research in Bangladesh and the information about salt-stress tolerance potentiality of PR is absent. Here, we investigated salt stress-induced changes in PR to unravel its stress tolerance potentiality. The results of PR were compared with those of green rice (BRRI dhan28). The effects of salt stress (e.g., 0 mM, 50 mM, 100 mM, and 150 mM NaCl) on both PR and BRRI dhan28 were observed. Under salt stress condition, the shoot and root lengths of PR and BRRI dhan28 were decreased compared to control but the percent reduction of shoot and root length of PR was significantly lowered than that of BRRI dhan28; the number of live leaves per tiller was higher in PR than BRRI dhan28; the plant height of PR was significantly lower than BRRI dhan28. The results of biochemical analysis showed that the proline content in PR was higher in non-stress condition but was lower at 100 mM and 150 mM NaCl stress compared to BRRI dhan28. Catalase activity and anthocyanin content were significantly higher in leaves of PR than those of BRRI dhan28 in both salt-stress and non-stress conditions. Moreover, total chlorophyll content was higher in PR than BRRI dhan28 in control condition. Taken together, these results suggest that PR rice has higher salt tolerance potentiality than green rice (BRRI dhan28). J Bangladesh Agril Univ 19(1): 53–60, 2021 https://doi.org/10.5455/JBAU.51377